Kontribusi dan Kritik Tafsir Kontemporer - Hadi Mutamam (AL-Fikr, 2013)
The emergence of contemporary interpretation methods of the Qur’an is triggered by, among others, concerns about the output when the interpretation is conducted textually, without taking into account the situation and background of a verse revelation as important historical data. A contemporary interpretation method is the technique of Qur’anic interpretation which places existing humanity issues as its spirit of explication. The current article implements a historical approach with a discourse critical method (content analysis). This contemporary interpretation method, which is a continuation of the modern exegesis, has a relatively long historical root. The history of modern interpretation stems from the emergence of Islamic modernization, which was itself prompted by modernization and renaissance emerging in the West. Modernization of interpretation arises as a result of dissatisfaction on the part of modern commentators upon the works of earlier commentators. The modern commentators argue that the product of earlier commentators do not touch the actual problems of people. Thus, the essence of the modernization of interpretation is criticism of classical interpretations.